Possibilities of cross-border activities of Fire Rescue Service of the South Bohemian region - Kavan, Štěpán (Vysoká škola bezpečnostného manažérstva v Košiciach, 2018)
The paper „Possibilities of cross-border activities of Fire Rescue Service of the South Bohemian region“ reflects the theme of possibilities of cross-border cooperation and activities which is focused to the fire protection, civil protection and crisis management. International cooperation is dealt with in the border regions of the South Bohemian Region, especially on the basis of examples of international cooperation. The cross-border cooperation is perceived as supporting and additional instrument of national system of civil protection.
Možnosti přeshraniční spolupráce Hasičského záchranného sboru Jihočeského kraje
Keywords: Fire Rescue Service of South Bohemia; Civil Protection; Cross-border Cooperation; Hasičský záchranný sbor Jihočeského kraje; ochrana obyvatelstva; přeshraniční spolupráce